The Effect of Electron versus Hole Photocurrent on Optoelectric Properties of p+-p-n-n+ Wz-GaN Reach-Through Avalanche Photodiodes. (25th March 2013) - Ghosh, Moumita; Mondal, Mangolika; Acharyya, Aritra
Abstract : The authors have made an attempt to investigate the effect of electron versus hole photocurrent on the optoelectric properties ofp + - p - n - n + structured Wurtzite-GaN (Wz-GaN) reach-through avalanche photodiodes (RAPDs). The photo responsivity and optical gain of the devices are obtained within the wavelength range of 300 to 450 nm using a novel modeling and simulation technique developed by the authors. Two optical illumination configurations of the device such as Top Mounted (TM) and Flip Chip (FC) are considered for the present study to investigate the optoelectric performance of the device separately due to electron dominated and hole dominated photocurrents, respectively, in the visible-blind ultraviolet (UV) spectrum. The results show that the peak unity gain responsivity and corresponding optical gain of the device are 555.78 mA W −1 and9.4144 × 10 3, respectively, due to hole dominated photocurrent (i.e., in FC structure); while those are 480.56 mA W −1 and7.8800 × 10 3, respectively, due to electron dominated photocurrent (i.e., in TM structure) at the wavelength of 365 nm and for applied reverse bias of 85 V. Thus, better optoelectric performance of Wz-GaN RAPDs can be achieved when the photocurrent is made hole dominated by allowing the UV light to be shined on then + -layer instead ofp + -layer of the device.